2021
DOI: 10.3390/ijms22031226
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Reveals Fast Changes in Salicylate and Jasmonate Signaling Pathways in Shoots of Carbonate-Tolerant Arabidopsis thaliana under Bicarbonate Exposure

Abstract: High bicarbonate concentrations of calcareous soils with high pH can affect crop performance due to different constraints. Among these, Fe deficiency has mostly been studied. The ability to mobilize sparingly soluble Fe is a key factor for tolerance. Here, a comparative transcriptomic analysis was performed with two naturally selected Arabidopsis thaliana demes, the carbonate-tolerant A1(c+) and the sensitive T6(c−). Analyses of plants exposed to either pH stress alone (pH 5.9 vs. pH 8.3) or to alkalinity caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…Increasing evidence indicated that above-ground plant parts can quickly respond to pH stress via regulating its growth and signal exchange between leaf and root [ 46 ]. To explore how ARF genes affect the adaption of above-ground tissues to pH switch, the young leaves of tissue culture seedlings were used to investigate their responses to pH shift (pH 4.8, 5.2, 5.8, 6.8) in V. corymbosum .…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence indicated that above-ground plant parts can quickly respond to pH stress via regulating its growth and signal exchange between leaf and root [ 46 ]. To explore how ARF genes affect the adaption of above-ground tissues to pH switch, the young leaves of tissue culture seedlings were used to investigate their responses to pH shift (pH 4.8, 5.2, 5.8, 6.8) in V. corymbosum .…”
Section: Resultsmentioning
confidence: 99%
“…The ability to mobilize poorly soluble Fe is key to tolerance. In the work of Pérez-Martín et al [30], a comparative transcriptomic analysis performed on two Arabidopsis thaliana genotypes (carbonate-tolerant and -susceptible) revealed that bicarbonate rapidly induces Fe deficiency-related genes in the susceptible genotype. In contrast, the tolerant line showed a differential expression of gene for receptor-protein-like, jasmonate, and salicylate pathways; sulfur starvation; and starch degradation, suggesting that carbonate-tolerant plants do not sense Fe deficiency rapidly.…”
Section: Nutrient Stressmentioning
confidence: 99%
“…In many cases, enough Fe is translocated from the roots to the leaves, and the efficiency of the leaf Fe is critical [ 32 ]. There is now enough evidence that this efficiency is related to the pH in the leaf apoplast and to the activity of the plasma membrane–located Fe reductase [ 33 ]. See also ref.…”
Section: Resultsmentioning
confidence: 99%